Learning Strategies for the Development of the Autonomy of Secondary School Students - Maldonado-Sánchez, Milagros (2019)
The objective of this research was to determine the predominant learning strategy that is related to the development of the autonomy of students belonging to the seventh semester from a public educational institution in Lima. It was developed as a substantive research and with a quantitative approach. Its design was non-experimental and cross-sectional-correlational. The population consisted of 171 students, to whom two questionnaires were applied. The results showed that the information coding strategy has more weight on the development of the autonomy of the students in question. Likewise, it is a risk strategy that means that a student who does not manage it, he will always present low levels of autonomous learning.